Characteristics of relevance for health in Turkish and Middle Eastern adolescent immigrants compared to Finnish immigrants and ethnic Swedish teenagers - Holmberg, Lars I; Hellberg, Dan (The Turkish Journal of Pediatrics, 2008)
Our objective was to compare sociodemographic conditions and risky/health behaviors affecting Turkish or Middle Eastern versus ethnic Swedes and Finnish immigrant adolescents, respectively. All eligible adolescents 13-18 years old (3,216 pupils) in a medium-sized town in Sweden completed a validated in-depth questionnaire (Q90), with 165 questions. One hundred and one adolescents were Turkish or Middle Eastern immigrants, while 73 were immigrants from Finland, a neighboring country to Sweden. Turkish/Middle Eastern immigrants were more likely to attend a theoretical program in school, were rarely bullied, as compared to ethnic Swedes and Finns. Turkish/Middle Eastern girls used alcohol at a lower frequency, and reported less depression and sexual experiences than ethnic Swedish girls and Finns. A higher frequency of Finnish adolescents had been bullied and had vandalized, and Finnish adolescents were also determined to have used tobacco and cannabis and to be heavy drinkers more frequently than boys from Turkey/the Middle East. We concluded that adolescent immigrants from Turkey and the Middle East seem to be well adapted to Sweden and also have ambitions for a higher education. Differences in risky behaviors were particularly pronounced in comparisons with immigrants from Finland for both boys and girls.